Insecticidal activity of Stemona collinsiae root extract against Parasarcophaga ruficornis (Diptera: Sarcophagidae) - Aurapa Sakulpanich (2018)
© 2017 Elsevier B.V. In Thai indigenous knowledge, Stemona plant has traditionally been used as insecticide on plantations. Recently, S. collinsiae extract was showed to be an anti-feedant and growth inhibitor and to exert strong insecticidal activity. Here, the insecticidal activity of S. collinsiae root extract against Parasarcophaga ruficornis is studied. The larvicidal and pupicidal activities of the ethanolic root extract of S. collinsiae were tested using contact toxicity tests, and adulticidal activity was tested using the topical contact toxicity and sugar bait methods The ethanolic extract at concentration ranging of 0.3–320 mg/larva for the direct contact toxicity test and from 0.3 to 3.2 mg/cm2/larva for the secondary contact toxicity test showed 3.0–51.0 and 1.0–94.0% corrected mortality, respectively. Against third-instar larvae, the LD50 concentrations of the ethanolic extract were 31.7 ± 0.0 mg/larva and 1.4 ± 0.0 mg/cm2/larva for direct and secondary contact toxicity tests, respectively. Pupae were not eliminated at all concentrations of the ethanolic extract. Against adult flies, which were killed via oral administration, the LD50 concentration of the ethanolic extract was 0.145 ± 0.070 g extract/g glucose. Thus, the ethanolic extract of S. collinsiae was capable of eliminating P. ruficornis in larval and adult stages via topical and ingestion administration, respectively.